Development of Systematic Sustainability Assessment (SSA) for the Malaysian Industry - Faiz, Mohd Turan; Kartina, Johan; Wan Nurul Syahirah, Wan Lanang; Nik Hisyamudin, Muhd Nor (IOP Publishing, 2016)
Sustainability assessment is recognized as a powerful and important tool to measure the performance of sustainability in a company or industry. There are various initiatives exists on tools for sustainable development. However, most of the sustainability measurement tools emphasize on environmental, economy and governance aspects. Some of the companies also implement different of sustainability indicators to evaluate the performance of economy, social and environmental separately. In this research, a new methodology for assessing sustainability in the context of Malaysian industry has been developed using integration of Green Project Management (GPM) P5 Integration Matrix, new scale of "Weighting criteria" and Rough-Grey Analysis. This systematic assessment will help the engineers or project managers measure the critical element of sustainability compliance.